2011
DOI: 10.1039/c0jm02772c
|View full text |Cite
|
Sign up to set email alerts
|

Rigid, conjugated and shaped arylethynes as mediators for the assembly of gold nanoparticles

Abstract: The ability to control and tailor the interparticle structures and properties of molecularly-mediated assembly of nanoparticles in terms of molecular size, shape, and structure is essential for exploring the nanostructured multifunctional properties. This report describes the results of an investigation on how such molecular size, shape, and structure are operative in the assembly of gold nanoparticles mediated by rigid methylthio arylethynes (MTAs) of different shapes (e.g., I, V, Y, and X shapes). The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Previous studies have highlighted the importance of the molecular geometry of CLs, but not their electronic properties. [14,15,31] Furthermore, the significant differences between the water and toluene systems show that the capping layer-solvent combination are also pivotal parameters that affect the aggregation of AuNPs. Although the precise role of each individual reaction parameter (namely capping layer, solvent, CL) is not fully understood, they can be applied to control the level of AuNP aggregation.…”
mentioning
confidence: 99%
“…Previous studies have highlighted the importance of the molecular geometry of CLs, but not their electronic properties. [14,15,31] Furthermore, the significant differences between the water and toluene systems show that the capping layer-solvent combination are also pivotal parameters that affect the aggregation of AuNPs. Although the precise role of each individual reaction parameter (namely capping layer, solvent, CL) is not fully understood, they can be applied to control the level of AuNP aggregation.…”
mentioning
confidence: 99%
“…Previous studies have highlighted the importance of the molecular geometry of CLs, but not their electronic properties 14. 15, 31 Furthermore, the significant differences between the water and toluene systems show that the capping layer–solvent combination are also pivotal parameters that affect the aggregation of AuNPs. Although the precise role of each individual reaction parameter (namely capping layer, solvent, CL) is not fully understood, they can be applied to control the level of AuNP aggregation 25.…”
Section: Methodsmentioning
confidence: 99%
“…Yan and co-workers reported the synthesis of rigid quadratic and trigonal planar linkers but, instead of binding three or four gold nanoparticles, the chelating effect allowed only two particles to be bridged. 12 In contrast, Novak et al reported the successful formation of dimers and trimers with similar linkers. 13 Here we report the synthesis of a tetrahedral molecule.…”
mentioning
confidence: 92%